2018
DOI: 10.9734/asrj/2018/v1i2681
|View full text |Cite
|
Sign up to set email alerts
|

Critical Moisture Content, Bulk Density Relationships and Compaction of Cultivated and Uncultivated Soils in the Humid Tropics

Abstract: Soil compaction affects soil fertility through increasing bulk density and soil strength. It also decreases infiltration rate, total porosity and amount of water stored in the root zone for crop use. In this study, we evaluated the optimum moisture contents (OMC) in relation to maximum dry density (MDD) and compaction of cultivated and uncultivated soils. The study was carried out on four land use types viz: uncultivated: Velvet tamarind (Dialium quineese), rubber plantation (Hevea brasiliensis) and cultivated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
(18 reference statements)
3
0
0
Order By: Relevance
“…A strong negative correlation at 1% level exists between MDD and each of NMC and OMC (Table 3). Similar negative correlation between MDD and OMC was also reported for soil in the humid tropics by Udom and Ehilegbu [78], and Al-Obaidi et al [79].…”
Section: Results Of Statistical Analysissupporting
confidence: 85%
See 1 more Smart Citation
“…A strong negative correlation at 1% level exists between MDD and each of NMC and OMC (Table 3). Similar negative correlation between MDD and OMC was also reported for soil in the humid tropics by Udom and Ehilegbu [78], and Al-Obaidi et al [79].…”
Section: Results Of Statistical Analysissupporting
confidence: 85%
“…Table 3 also shows that strong positive relation exists between OMC and permeability (0.797). Highly significant positive relationship between the OMC and permeability was also reported by Udom and Ehilegbu [78].…”
Section: Results Of Statistical Analysissupporting
confidence: 64%
“…soil Bd was significantly lower than in TA soil through several sowings [15]. In this study, the first and second soil layers (on the 2nd sampling of M°) showed negative correlations of Bd and M° (r = −0.67 and −0.65), coinciding with other studies, probably due to when Bd increases, porosity decreases, reducing space for moisture [66,67]…”
Section: Bulk Density (Bd)supporting
confidence: 89%